2016
DOI: 10.1007/s12576-016-0497-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of quercetin on the gene expression of the GABAA receptor α5 subunit gene in a mouse model of kainic acid-induced seizure

Abstract: The flavonoid quercetin has recently been reported to have neuroprotective effects, and the role of the gamma-aminobutyric acid A alpha 5 subunit (GABA α5) receptor has been determined in some nervous system disorders. The aim of this study was to identify the molecular mechanism of the effect of quercetin administered at anticonvulsive doses on the expression of the GABA α5 receptor gene in kainic acid (KA)-induced seizures in mice. The experimental animals were divided into four groups: control, KA, and KA +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…Flavonoids have also been shown to exert anticonvulsive and antioxidant effects [41]. In a recent study, quercetin was found to decrease seizure activity in a mouse model of KA-induced seizure by modulating the gene expression of the GABA A receptor [42]. Another study also showed that flavonoids are neuroprotective agents that modulate GABA receptors in experimental models of epilepsy [43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids have also been shown to exert anticonvulsive and antioxidant effects [41]. In a recent study, quercetin was found to decrease seizure activity in a mouse model of KA-induced seizure by modulating the gene expression of the GABA A receptor [42]. Another study also showed that flavonoids are neuroprotective agents that modulate GABA receptors in experimental models of epilepsy [43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several pharmacological activities of quercetin have been described, such as neuroprotective activity [54,55]. In addition, the effect of quercetin pretreatment on the gene expression of the beta subunits of γ-amino butyric acid receptor type A (GABA A ) has been studied in the context of seizures induced by KA, and the results showed that quercetin at a dose of 100 mg/kg modulated the expression of the β1 and β3 subunits of the GABA A receptor in the KA model [42]. Some studies have demonstrated new pharmacological effects of quercetin related to pain inhibition, cytokine production, and oxidative stress that lead to reductions in neuroinflammation; however, there is also evidence that quercetin metabolites reach the cerebrospinal fluid after peripheral treatment.…”
mentioning
confidence: 99%
“…In that study, 20 mg/kg of quercetin administered 30 min before picrotoxin injection had anticonvulsant effects. Moreover, in another study with KA-induced model mice, it was shown that quercetin administration (50 and 100 mg/kg/d, intraperitoneally for 7 d) decreased seizure severity in a dose-dependent manner; in addition, it reduced the expression levels of the GABA A α 5 mRNA (111). Other studies have also reported an increase in GABA A α 5 expression in KA and pilocarpine models (112–114), suggesting that compensatory mechanisms are involved in disease pathogenesis (114).…”
Section: Using Flavonoids To Treat Epilepsy and Seizuresmentioning
confidence: 99%
“…Treatment with QC (50 mg and 100 mg/kg) reduced the KA-induced increase of GABAA α5 expression. According to these results, the expression of the GABAAα5 receptor could be a potential target of QC to reduce or to serve as a marker of seizure severity [86].…”
Section: Potential Therapeutic Targets Of Quercetinmentioning
confidence: 99%